A case study of packaging waste collection systems in Portugal – Part I: Performance and operation analysis. (March 2017) - Martinho, Graça; Gomes, Ana; Santos, Pedro; Ramos, Mário; Cardoso, João; Silveira, Ana; Pires, Ana
Highlights: Compare mixed and drop-off waste collection systems in Portugal. Use performance and operation indicators for logistics and recycling. Mixed is better in performance indicators and worse in operation indicators. System optimizations and citizen awareness campaigns are needed. Abstract: The need to increase packaging recycling rates has led to the study and analysis of recycling schemes from various perspectives, including technical, economic, social, and environmental. This paper is part one of a three-part study devoted to comparing two recyclable packaging waste collection systems operating in western Portugal: a mixed collection system, where curbside and drop-off collections are operated simultaneously (but where the curbside system was introduced after the drop-off system), and an exclusive drop-off system. This part of the study focuses on analyzing the operation and performance of the two waste collection systems. The mixed collection system is shown to yield higher material separation rates, higher recycling rates, and lower contamination rates compared with the exclusive drop-off system, a result of the curbside component in the former system. However, the operational efficiency of the curbside collection in the mixed system is lower than the drop-off collection in the mixed system and the exclusive drop-off system, mainly because of inefficiency of collection. A key recommendation is to ensure that the systems should be optimized in an attempt to improve performance. Optimization should be applied not only to logistical aspects but also to citizens' participation, which could be improved by conducting curbside collection awareness campaigns in the neighborhoods that have a mixed system.